Light-responsive azobenzene-based glycopolymer micelles for targeted drug delivery to melanoma cells. (August 2015) - Pearson, Samuel; Vitucci, Dylan; Khine, Yee Yee; Dag, Aydan; Lu, Hongxu; Save, Maud; Billon, Laurent; Stenzel, Martina H.
Abstract : Graphical abstract: Highlights: Light-responsive block copolymers were synthesised by RAFT polymerisation. The hydrophobic azobenzene and hydrophilic β-galactose block lengths were varied. All block copolymers self-assembled into small (<50 nm) spherical micelles. Nile red was encapsulated in the micelle cores and used to monitor cellular uptake. Micelles showed low toxicity and successful internalisation by A375 melanoma cells. Abstract: Light-responsive glycopolymer micelles were produced by the self-assembly of amphiphilic block copolymers containing azobenzene and β-galactose units. These well-defined block copolymers were synthesised firstly by the RAFT polymerisation of an azobenzene methacrylate monomer (AzoMA) to produce two short azobenzene macroRAFT agents containing 7 and 15 monomer units. Chain extension with a second block of ∼150 or ∼250 sugar units comprising of a protected β-galactose monomer (β-AcGalEtMA) generated four block copolymers, which were converted to amphiphilic structures by deprotection of the acetyl groups on the sugar units. Micelles with well-defined sizes of 26–50 nm were produced by self-assembly in water. The azobenzene units isomerised very rapidly to their more polar cis isomers under UV irradiation, reaching the photostationary state within 2 min, with reversion to the trans state taking several hours in the dark. This transition to the more polar cis state is an important criteria for aiding expulsion of a hydrophobic payload. In cell studies, unloaded micelles showed low cytotoxicity, and micelles loaded with the model hydrophobic compound Nile red demonstrated high cellular uptake in human melanoma A375 cells, demonstrating their suitability as a potential drug delivery system for melanoma.